Fotograficzna enklawa. Nowy Jork i jego mieszkańcy w soczewce aparatu - Sulejewska, Justyna (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2013)
The title phrase “photographic enclave” expresses the condition of projects that tell about a city using a photographic medium. The article discusses three audiovisual works that use photos to portray New York and its inhabitants: Smoke by Wayne Wang and Paul Auster, Stefan Nadelman’s Terminal Bar, and the multimedia project One in 8 Million. The works represent a variety of film models (drama, documentary, interactive media), and their authors use the formal and cognitive aspects of photography in a different ways. The aim of the article is to analyze the function of photography for portraying urban communities and to see if this treatment was successful.

Tytułowa „fotograficzna enklawa” wyraża kondycję projektów, które podejmując tematykę miejską opierają się na medium fotograficznym. Artykuł omawia trzy dzieła audiowizualne, które opowiadając o Nowym Jorku i jego mieszkańcach wykorzystują w tym celu zdjęcia: Dym Wayne'a Wanga i Paula Austera, Terminal Bar Stefana Nadelmana oraz projekt multimedialny One in 8 Milion. Dzieła reprezentują odmienne modele filmowe (fabuła, dokument, media interaktywne), a ich autorzy w różny sposób odwołują się do formalnych i poznawczych aspektów fotografii. Celem artykułu jest zanalizowanie, jaką funkcję pełni fotografia przy portretowaniu miejskiej społeczności oraz na ile jest to zabieg udany.
Photographic enclave. New York City and its inhabitants through camera lens
Keywords: Terminal Bar; Stefan Nadelman; Smoke; Wayne Wang; Paul Auster; One in 8 Million; photography; New York in film; fotofilm; fotografia; Nowy Jork w filmie